PERANAN SEKTOR PARIWISATA DALAM PENINGKATAN PENDAPATAN ASLI DAERAH DI KAWASAN INDONESIA TIMUR - Chan, Nuraini (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
This study aims to examine the impact of the tourism sector on Local Own-Source Revenue (PAD) in eastern Indonesia, focusing on variables such as tourist arrivals, average length of stay, number of hotels and other accommodation options, and financial factors, particularly capital expenditures and Regional Gross Domestic Product (RGDP). This research primarily utilizes secondary data as the main information source, covering five independent variables: the number of foreign and domestic tourists, average length of stay, number of hotels and other accommodations, capital expenditures, and RGDP. To achieve the research objectives, panel data regression analysis was applied using the Fixed Effects Model (FEM) approach. The findings show that the variables for foreign and domestic tourist numbers, average length of stay, number of hotels, and capital expenditures align with the hypothesized relationships, achieving significance levels at various confidence intervals—1%, 5%, and 10%. However, the RGDP variable exhibited a relationship direction that did not align with the hypothesis, with significance at a 1% confidence level